GROWTH PERFORMANCE OF LABEO ROHITA (HAM.) FINGERLINGS FED WITH FERMENTED AND NON-FERMENTED DIETS - SHARMA,, O P; NAIR, PREETI; JAIN, H K (Journal of the Inland Fisheries Society of India, 2021)
In fish culture, the cost of feed accounts for 50-60% of the total cost of production. Much work has been done on the nutritional requirementsof various fish species, but studies on fermented feeds are very less (Pullin, 1987; Srinivasan, 1987; Ayyappan et al; 1990; Kumar and Sharma, 1999; Sharma and Kishan, 2006; Kathar et al., 2008). The feed materials, when fermented, become rich in microbial population and nutrients, especially protein. It also enhances immunity by increasing activity of haemocytes and inhibits the growth of toxin producing microbes and improves nutrient utilization. Studies have shown significant effects of microbial communities on the growth of fish (Malik, 1992; Kumar, 1994; Sharma and Kumar, 1998; Kumar and Sharma, 1999). Fermented feed is more digestible and rich in nutrient as compared to non-fermented ones and are more favourableto fish growth (Kishan, 2000).